(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2020)
The goal of the research was to analyze, through textual strategies, how the political-ideological use of football happened in the federal government advertisement "This is to be Brazilian. This is the Cup of the Cups", conveyed on the television media in 2014. For this, was used the Physical Cultural Studies’ assumptions. The analysis showed that the sport was used by the Federal Government with political-ideological purposes. Thus, was identified the reinforcement of the sense of patriotism, the presence of intentionalities aimed at promoting the acceptation of the World Cup in Brazil and intertextual relations aimed at conveying a positive idea of the PT government, political party that was in the power of the State and would be compete for reelection in 2014.